2016
DOI: 10.1002/dc.23523
|View full text |Cite
|
Sign up to set email alerts
|

Cytomorphology, clinicopathologic, and cytogenetics correlation of myelomatous effusion of serous cavities: A retrospective review

Abstract: ME in PCM can present early in the natural history of the disease or very late. The preponderance of IgA-myeloma and complex-cytogenetics abnormalities is a noteworthy finding. Although there are different hypotheses regarding how ME develops in PCM, our finding supports the hypothesis that direct spread of PCM into serous cavities is a likely mechanism. Diagn. Cytopathol. 2016;44:742-747. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Pleural effusions are rarely associated with MM and most often signify a concurrent disease process. MPE are even more unusual, they occur in <1% of the cases, and carry a poor prognosis . The first case of pleural effusion and involvement of serous cavities in MM was reported in 1994 by Rodriguez et al Nevertheless, the incidence of PME could be higher than that reported by Kintzer et al and could depend on the method of detection.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Pleural effusions are rarely associated with MM and most often signify a concurrent disease process. MPE are even more unusual, they occur in <1% of the cases, and carry a poor prognosis . The first case of pleural effusion and involvement of serous cavities in MM was reported in 1994 by Rodriguez et al Nevertheless, the incidence of PME could be higher than that reported by Kintzer et al and could depend on the method of detection.…”
Section: Discussionmentioning
confidence: 91%
“…The first case of pleural effusion and involvement of serous cavities in MM was reported in 1994 by Rodriguez et al Nevertheless, the incidence of PME could be higher than that reported by Kintzer et al and could depend on the method of detection. Indeed, modern methods such as flow cytometry could allow for the determination of the clonal nature of the disease …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PEs due to plasma cells infiltration are rare, with approximately 80 cases reported worldwide [8,27,28]. It may result from extension of adjacent subcutaneous, skeletal, or parenchymal plasmocytomas into the pleural space [8,13].…”
Section: Discussionmentioning
confidence: 99%
“…However, the detection rates of these methods are generally low, so it is often necessary to carry out repeated tests to get more accurate results [ 6 ]. Moreover, the traditional imaging detections such as X-ray, ultrasound, and computed tomography (CT) can only detect diseases by relying on morphological changes, and it is impossible to achieve more effective inspections for early disease [ 7 , 8 ]. At this stage, medical diagnosis and treatment capabilities with the further advancement of E-health have been improved directly or indirectly from digital medical equipment to high-level information and knowledge sharing, and various digital imaging and postprocessing technologies make disease diagnosis more intuitive and accurate.…”
Section: Introductionmentioning
confidence: 99%